Substantiating the roles of higher education system in Malaysia: identifying issues and charting the way forward - Abdul Rahman, Shukran; Khalid, Haniza; Mohd Yusof, Danial (2017)
Education is one of the key factors for national transformation and advancement. Higher education (HE) stands as an important sector in any country including Malaysia, which roles range from workforce supplier to knowledge and innovation centers. During the early days of HE, focus has been given to producing knowledgeable workforce but over time, the roles have changed to producing new knowledge and solving societal problems. Though many expect HE to produce more knowledgeable and competent graduates, the country’s strategic way forward has made it imperative for HE sector to be significant players that drive transformation. We argue that the role of HE is beyond producing workforce, but to help the country in shaping the advancement of social growth and economic prosperity through various academic activities, especially research and innovation. This paper addresses issues in the current Malaysian HE landscape, in terms of its research and development activities. The paper also highlight various future global scenario that necessitate the active roles of HE in research and development agenda. The paper also addresses whether the current agenda on research and development is relevant to the country’s direction, or suitable to address the needs of various stakeholders. The findings will enlighten the HE authority of the issues that require proper attention, and in turn steer the direction of HE services.